Biological features of fowl adenovirus serotype-4 - Rashid, Farooq; Xie, Zhixun; Wei, You; Xie, Zhiqin; Xie, Liji; Li, Meng; Luo, Sisi (Frontiers in Cellular and Infection Microbiology, 2024)
Fowl adenovirus serotype 4 (FAdV-4) is highly pathogenic to broilers aged 3 to 5 weeks and has caused considerable economic loss in the poultry industry worldwide. FAdV-4 is the causative agent of hydropericardium-hepatitis syndrome (HHS) or hydropericardium syndrome (HPS). The virus targets mainly the liver, and HPS symptoms are observed in infected chickens. This disease was first reported in Pakistan but has now spread worldwide, and over time, various deletions in the FAdV genome and mutations in its major structural proteins have been detected. This review provides detailed information about FAdV-4 genome organization, physiological features, epidemiology, coinfection with other viruses, and host immune suppression. Moreover, we investigated the role and functions of important structural proteins in FAdV-4 pathogenesis.Finally, the potential regulatory effects of FAdV-4 infection on ncRNAs are also discussed.